2021
DOI: 10.3389/fmolb.2021.674863
|View full text |Cite
|
Sign up to set email alerts
|

CCDC137 Is a Prognostic Biomarker and Correlates With Immunosuppressive Tumor Microenvironment Based on Pan-Cancer Analysis

Abstract: BackgroundThe coiled-coil domain containing (CCDC) family proteins have important biological functions in various diseases. However, the coiled-coil domain containing 137 (CCDC137) was rarely studied. We aim to investigate the role of CCDC137 in pan-cancer.MethodsCCDC137 expression was evaluated in RNA sequence expression profilers of pan-cancer and normal tissues from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database. The influence of CCDC137 on the prognosis of tumor patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…CCDC137, as one vital member of coiled‐coil domain containing (CCDC) family proteins, was overexpressed and positively associated with worse prognosis in various tumour types, such as liver hepatocellular carcinoma, lower grade glioma and prostate adenocarcinoma. 46 Similarly, we observed that CCDC137 expression was elevated in liver metastatic CRC patients and positively correlated with advanced tumour stages and lymph node metastatic stages of CRC. Furthermore, the overexpressed CCDC137 was significantly correlated with short disease‐free survival as shown in TCGA database.…”
Section: Discussionsupporting
confidence: 57%
“…CCDC137, as one vital member of coiled‐coil domain containing (CCDC) family proteins, was overexpressed and positively associated with worse prognosis in various tumour types, such as liver hepatocellular carcinoma, lower grade glioma and prostate adenocarcinoma. 46 Similarly, we observed that CCDC137 expression was elevated in liver metastatic CRC patients and positively correlated with advanced tumour stages and lymph node metastatic stages of CRC. Furthermore, the overexpressed CCDC137 was significantly correlated with short disease‐free survival as shown in TCGA database.…”
Section: Discussionsupporting
confidence: 57%
“…TGFβ signaling plays a major role in shaping the immunosuppressive tumor microenvironment [ 80 , 81 ]. Through transduction of IL10-induced signaling, IL10RB (IL10 receptor subunit beta) contributes to the immunosuppressive tumor microenvironment [ 82 , 83 ]. Consistent with this knowledge, BIRC5, MXD3, and RECQL4 expressions positively correlate with IL10RB expression ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated evidence indicated that the fraction of immune cells in the TME could serve as a marker for the diagnosis and prognosis of a variety of malignant tumors ( 48 , 49 ). However, some prognostic models based on the TME were developed in the setting of a pan-cancer analysis ( 50 , 51 ); they might not be the most optimal choice for CM. In addition, not all fractions of the TME exert a significant impact on the prognosis of tumors.…”
Section: Discussionmentioning
confidence: 99%